Do Filipinos Really Hate Duterte’s Leadership? Uncovering Duterte Controversies in the Philippines - Givheart Dano (Journal of Asian Social Science Research, 2023)
This article investigates whether Filipinos genuinely have negative feelings about President Duterte’s leadership. It examines public opinions through surveys, media discussions, and actions in socio-political groups. Using a descriptive research approach, this article aims to understand diverse perspectives on Duterte’s leadership in the Philippines. It delves into why some people support him and others criticize him, considering factors like economic policies, leadership style, and responses to significant events during his presidency. This article seeks to uncover the various reasons that influence people’s opinions in a changing political and social landscape in the Philippines. It recognizes that different factors shape Filipinos’ beliefs about their leader. Finally, it offers insightful perspectives into the complex sentiments surrounding Duterte’s leadership, providing a clearer understanding of what Filipinos truly think about their president.